HUBUNGAN KOMPETENSI GURU TERHADAP PRESTASI BELAJAR SISWA SMP NEGERI 3 TAKKALALLA KABUPATEN WAJO - Aisyah Nursyam (EKSPOSE, 2018)
This study is a correlational study that aims to see the relationship of teacher competency to student achievement in SMP Negeri 3 Takkalalla in the second semester of the 2017/2018 school year in Wajo district. The hypothesis of this study is if H0: There is a significant relationship between teacher competency on student achievement and if H1: There is no significant relationship between teacher competency and student achievement. The data collection technique carried out in this study is a questionnaire that is a list of statements given to other people who are willing to respond according to user requests and documentation to obtain existing data, namely documentation of student grades in the even semester of the 2017/2018 school year and relevant data others. Based on the results of the product moment correlation analysis, the relationship of teacher competence to the learning achievement of students of SMP Negeri 3 Takkalalla in Wajo district obtained a calculated value of -2.59. While the table is 1.66462 at a significant level of 5% and N = 80. From the results of the analysis, it can be seen that the calculated value table (-2.59 1,99085). Based on the analysis, it can be concluded that there is no relationship between teacher competency and student achievement in SMP Negeri 3 Takkalalla district Wajo 2017/2018 Academic Year